1001 practice problems chemistry - Hattori, Heather 19XX-; Langley, Richard 1948- (John Wiley & Sons, Inc., 2022)
Intro -- Title Page -- Copyright Page -- Table of Contents -- Introduction -- What You'll Find -- Beyond the Book -- Where to Go for Additional Help -- Part 1 The Questions -- Chapter 1 Units and Unit Conversions -- The Problems You'll Work On -- What to Watch Out For -- Understanding Metric Prefixes and Units -- Choosing Appropriate Units -- Doing Metric Conversions -- Converting between Systems of Measurement -- Using Dimensional Analysis -- Chapter 2 Scientific Notation and Significant Figures -- The Problems You'll Work On -- What to Watch Out For -- Putting Numbers in Scientific Notation -- Taking Numbers out of Scientific Notation -- Calculating with Numbers in Scientific Notation -- Recognizing Significant Figures -- Writing Answers with the Right Number of Sig Figs -- Chapter 3 Matter and Energy -- The Problems You'll Work On -- What to Watch Out For -- Phases of Matter and Phase Changes -- Classifying Substances and Mixtures -- Properties of Matter -- Calculating Density -- Working with Energy -- Chapter 4 The Atom and Nuclear Chemistry -- The Problems You'll Work On -- What to Watch Out For -- Isotopes and Subatomic Particles -- Electrons and Quantum Mechanics -- Average Atomic Mass -- Nuclear Reactions and Nuclear Decay -- Completing Nuclear Reactions -- Half-Lives -- Chapter 5 Periodicity and the Periodic Table -- The Problems You'll Work On -- What to Watch Out For -- Element Symbols and Names -- Structure of the Periodic Table -- Periodic Trends -- Chapter 6 Ionic Bonding -- The Problems You'll Work On -- What to Watch Out For -- Naming Binary Compounds -- Naming Compounds with Polyatomic Ions -- Writing Formulas of Binary Compounds -- Writing Formulas of Compounds with Polyatomic Ions -- Chapter 7 Covalent Bonding -- The Problems You'll Work On -- What to Watch Out For -- Prefixes in Covalent -Compound Names
Keywords: Chemie; Übung